Selected Recent Advances in the Utilization of Biopolymers for Nano‐ and Microfiber Materials and Nonwovens Production - Malte Winnacker (Macromolecular Materials and Engineering)
Abstract When the variety of synthetic polymers came up in the 20th century, they expectedly replaced many fiber materials which were made so far from biopolymers since ancient times (e.g., for textiles, medical products, etc.). Meanwhile, to some extent, there is a strong revival of various fibers from biopolymers regarding their utilization for various applications, based on their interesting structures, availability, sustainability, costs, and other factors. Regarding bioeconomy and sustainability, there has thus been an intensive market dynamic for biopolymers. Therefore, especially a variety of fiber materials have recently been described that are based on different biopolymers as, e.g., polysaccharides and biopolyesters. For this, a variety of enhanced polymer structure modification and sophisticated processing methods are applied. Instead of a complete and comprehensive overview (which would be beyond the scope of this Perspective format), the aim of this article is to elucidate some selected recent advantages in this field and to focus on the special features of these examples.